Micro, Small, and Medium Enterprises (MSMEs) Center in East Kolaka with Emphasis on Neo-Vernacular Architecture - Nurhikmah, Hikmah; Nurbaity, Dian Puteri; Jurumai, La Pande (RUSTIC, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in enhancing community resources and advancing the economy in Indonesia. The purpose of this research is to analyze and describe the Micro, Small, and Medium Enterprises Development Center (MSMEC) in East Kolaka using a Neo-Vernacular emphasis. A qualitative descriptive method is applied in this study, with data obtained through observation, interviews, and documentation review related to the development and characteristics of the MSMEC in the area. The results of the study show that the MSMEC in East Kolaka not only functions as a place for economic activities but also as a center of social interaction that strengthens local identity. The application of Neo-Vernacular architecture in the design of the MSMEC building demonstrates a combination of tradition and modernity, creating a space that supports the sustainability of MSMEs and enhances the attraction for tourists. This research offers new perspectives in the development of policies and strategies to strengthen MSMEs in East Kolaka.